Reusing solar panels to improve access to information and communication in an off-grid village: A financial feasibility assessment. (November 2022) - Pandyaswargo, Andante Hadi; Wibowo, Alan Dwi; Onoda, Hiroshi
Abstract: Pursuing Sustainable Development Goal (SDG) number 7, to "Ensure access to affordable, reliable, sustainable and modern energy for all, " many off-grid villages received solar panels from external supports. However, these communities rarely have the capacity for reinvestment when the battery deteriorates. This study proposes reusing the abandoned solar panels as a power supply for cellphone charging stations and signal boosters. Taking an off-grid agricultural village in Indonesia as a case study, a cost–benefit analysis (CBA), net present value (NPV), and payback time estimation were conducted to determine the financial feasibility of the proposed strategy. The results identified that paired with an existing business, a four months payback time can be achieved under a standard scenario. Moreover, solar panels' end-of-life poses an environmental burden. A sustainable use that can take full advantage of the technology's lifespan should be considered when donating technologies to the bottom billions.